A comparative study between brick and stone aggregate concrete using rice husk ash as partial cement replacement. Issue 9 (13th September 2022) - Bhowmik, R.N.; Pal, J.
Abstract: Today's world cannot be imagined without the application of concrete. Although as a constituent of concrete stone aggregate is mostly used, there are certain areas on this earth where it is scarcely available which leads to the use of brick aggregate. Moreover, as supplementary cementitious material, use of rice husk ash is beneficial to our environment. So, the study presents the possibility of using the brick aggregate and rice husk ash to the possible extent in making concrete by comparing stone and brick aggregate concrete, with rice husk ash as partial cement replacement. The specimens were prepared using water to binder ratios varying from 0.38 to 0.54. Properties of fresh and hardened concrete were measured using different tests on the specimens.The results of the mechanical tests were also co‐related with the microscopic image studies.This study finds that for a higher grade of concrete optimum rice husk ash replacement varies between 5 % to 10 % and for lower grade of concrete the rice husk ash replacement varies between 10 % to 15 %. The study also shows that using rice husk ash, brick aggregate concrete exhibits better improvement in comparison to stone aggregate concrete. Abstract : This paper compares the mechanical properties of concrete, cast using different percentages of rice husk ash in both brick aggregate and stone aggregate. Later SEM analyses were also conducted to co‐relate with the experimental values.